Solanaceae endémicas del Perú - Knapp, Sandra (2006)
The Solanaceae are among the most diverse families in the Peruvian flora, with about 42 genera and 600 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly herbs and shrubs. Here we recognize as endemics 203 species and six varieties in 16 genera. This family ranks 6th among the most diverse families in endemic taxa. Solanum, Nolana and Jaltomata are the genera with more endemic species. Endemic taxa are found in almost all regions, mainly Mesoandean, Very Humid Montane Forests and Subtropical Costal Desert, from sea level 100 to 3800 m elevation. Thirty-six taxa have been recorded within Peru’s protected areas system.